Administrative Law by Vaclovas Biržiška - Deviatnikovaitė, Ieva (Teisė, 2018)
[only abstract in English; full article, abstract in Lithuanian] The article examines Administrative Law course descriptions from 1931/1932 and 1936/1937 academic years and lectures’ notes published in 1935 and 1937. These were the only written sources on the studies of administrative law until 1939. Despite such a miserable literature on the subject of administrative law in the Interwar period in Lithuania, it has not been analysed to date. The object of the research is the studies and the content of administrative law course unit in the Interwar period in Lithuania including getting acquainted with public administration of some areas. Several findings were made in the study. First, administrative law was not given enough attention – the head of Administrative Law Department at the University of Vytautas Magnus, V. Biržiška, was a recognized and well-known book scientist, documentarian, book and press historian, dean of the Faculty, but not a specialist of administrative law. Some young scholars (V. Fridšteinas, K. Račkauskas) were professionally interested in administrative law, although somehow they were not invited to teach at the University. Second, during the course of administrative law V. Biržiška devoted much attention to the history of the formation of various states, to the comparative legal regulation in different countries. That is the reason to call his course as a first course of comparative administrative law in Lithuania. Third, the course of V. Biržiška’s administrative law was right at its initial phase of development: there were no clear terms of administrative law, administrative acts, public service, public administration, and no clear division between administrative law and other branches of public and private law.